Artificial Intelligence Age in Healthcare is Here and Here to Stay - Mohammed Mosleh Uddin, Abu Noman (Journal of Armed Forces Medical College, Bangladesh, 2025)
Abstract not available JAFMC Bangladesh, Vol 20, No 2 (December) 2024:1-2